Post-Digital Literary Studies - Cramer, Florian (MATLIT: Materialities of Literature, 2016)
Digital humanities and digital literary studies face much the same challenges as contemporary media art: what will become of them once their media are no longer “new”, and the limitations of processing art as data have become more clearly and widely understood? This paper revisits information aesthetics and computer poetics from the 1960s and 1970s, casting them as precursors of today’s digital humanities, with many of the same issues, achievements and failures, and with their own hype cycles of boom and bust. Conversely, “post-digital” and “Post-Internet” trends in music, graphic design and visual arts may anticipate possible futures of digital humanities and literary studies after the hype has passed. DOI: http://dx.doi.org/10.14195/2182-8830_4-1_1